The effect of incorporating carbon nanotubes on impact, transverse strength, hardness, and roughness to high impact denture base material - Wsamaa S Mahmood (College of Dentistry/ University of Baghdad, 2015)
Background: One of the most common complications of dentures is its ability to fracture, so the aim of this study was to reinforce the high impact denture base with carbon nanotubes in different concentrations to improve the mechanical and physical properties of the denture base. Materials and methods: Three concentrations of carbon nanotubes was used 0.5%, 1%, 1.5% in a pilot study to see the best values regarding transverse strength, impact, hardness and roughness test, 1 wt% was the best concentration, so new samples for control group and 1wt% carbon nanotubes and the previous tests were of course repeated. Results: There was a significant increase in impact strength and transverse strength when we add carbon nanotubes in 1wt%, compared to control group where as hardness decrease when adding carbon nanotubes. Conclusion: the addition of carbon nanotubes improves the physical and mechanical properties. Key words: Carbon nanotubes, high impact denture base.